PENINGKATAN HASIL BELAJAR SISWA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD - Amelia Novianti, (Pendidikan Ekonomi, 2009)
The study is aimed to know  the use of Student Team Achievement Divisions (STAD) learning model to increase the eleventh graderslearning results  of the lesson material in accounting cycles of service companies at SMAN I Dringu. The data collection techniques were observation, questionnaires, interview, and tests. The data were then analyzed in descriptive qualitative manner. The findings indicated that the students learning activity and learning results increased. The students also have positive response toward the use of STAD in the learning process. Moreover, the teacher ability to manage the class with STAD was considered good.